Financial and Mental Health Concerns of Impoverished Urban-Dwelling Bangladeshi People During COVID-19 - Islam, Md. Saiful; Rahman, Md. Estiar; Banik, Rajon; Emran, Md. Galib Ishraq; Saiara, Noshin; Hossain, Sahadat; Hasan, M. Tasdik; Sikder, Md. Tajuddin; Smith, Lee; Potenza, Marc N. (Frontiers in Psychology, 2021)
Background: The COVID-19 pandemic has impacted the physical, mental and financial health of many individuals. Individuals living in impoverished crowded settings may be particularly vulnerable to COVID-19-related stressors. How substantially marginalized groups like impoverished urban-dwelling individuals are specifically impacted during this pandemic is poorly understood. The present study aimed to investigate correlates of financial concerns and symptoms of depression and posttraumatic stress disorder (PTSD) during the COVID-19 pandemic among impoverished urban-dwelling individuals residing in Dhaka, Bangladesh. Methods: A cross-sectional survey was conducted between August and September 2020 using face-to-face interviews in six disadvantaged neighborhoods (“slums”) in Dhaka. Individuals were interviewed using a structured questionnaire consisting of questions assessing socio-demographics, lifestyle, financial well-being relating to the COVID-19 pandemic, depression, and PTSD. Results: Four-hundred-and-thirty-five individuals (male=54.7%; mean age=45.0±12.0 years; age range=18-85 years) participated. Most (96.3%) reported that their household income decreased due to the COVID-19 pandemic. Factors associated with decreased household incomes included female gender, primary education, jobless, food scarcity and depression. Depression symptoms were linked to female gender, being jobless, being divorced, living in a joint family, excessive sleep and smoking. Low incomes, excessive sleep, joblessness and food scarcity were positively associated with PTSD symptoms. In contrast, less sleep appeared protective against PTSD. Conclusions: Public health initiatives, in particular mental health services that target stress, should be introduced to mitigate against potential financial and psychological effects of the pandemic on impoverished urban-dwelling individuals in Bangladesh.